Role of Minimally Invasive Surgery (Laparsocopic Surgery) in the Management of Acute Abdomen - Nasir Bakhtiar, Muhammad Tayyeb, Ahmad Arsalan Tahir, Tufail Ahmad, Muhammad Ishfaq, Asad Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study’s goal is to evaluate the diagnostic and therapeutic efficacy of non-invasive surgery (laparoscopy) in the treatment of acute abdomen. Methods: This is an observational study, conducted in Peshawar Medical College Group of Hospitals, Peshawar from January, 2020 to July, 2021. Total 60 patients presented with acute abdomen were included in the study. Patients underwent Laparoscopic surgery after initial work-up. The outcome of Laparoscopy was assessed in terms of diagnostic accuracy, conversion rate, inadvertent injury, hospital stay, wound infection and pain score. Result: Total 60 patients with acute abdomen underwent Laparoscopy during study period. Male to female ratio 1: 1.2 (27:33) while mean age was 36.18 years (12-75). In 93% (56/60) cases per-operative diagnosis was compatible with pre-operative diagnosis. The conversion rate from laparoscopic to open surgery was 1.6%. The average length of hospital stay was 1.45 days (1-4 days). On a visual analogue scale, the mean pre-operative pain level was 6.28. (3-9). On the first post-operative day, the mean post-operative pain score on a visual analogue scale was 1.68. (1-4). Infection at the port site occurred in 3.3% (2/60). Conclusion: Laparoscopy is a safe and effective method of diagnosing and treating acute abdomen so it can be safely adopted in patients presenting with acute abdomen as Laparoscopy eliminates diagnostic delays and unneeded laparotomy and its complications. Keywords: Acute Abdomen, Laparoscopy, Minimally Invasive Surgery, Laparotomy